1982
DOI: 10.1128/aac.21.6.887
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of mycophenolic acid and allopurinol against Leishmania tropica in human macrophages

Abstract: The possibility that purine inhibitors or analogs might be effective antileishmanial agents led to the determination of the antileishmanial activity of mycophenolic acid and allopurinol in vitro. The drugs were tested against Leishmania tropica amastigotes (mammalian forms) within human macrophages, a model in which achievable serum concentrations of antileishmanial agents currently in use eliminate approximately 90% of the parasites. Mycophenolic acid, an inhibitor of guanosine nucleotide synthesis from inosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
1
1

Year Published

1983
1983
2004
2004

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 18 publications
0
11
1
1
Order By: Relevance
“…IMPDH inhibitors are expected to mainly affect viral RNA and/or DNA synthesis when there is an increased need for synthesis, as in the case of virus-infected cells. IMPDH inhibition decreases levels of intracellular guanine nucleotide pools required for adequate RNA and DNA synthesis; therefore, inhibition of IMPDH with MPA has been shown to have antiproliferative (7), immunosuppressive (42), antimicrobial (43), antiviral (63,70), and antiparasitic (3,29) effects. Currently, MPA is used clinically to prevent rejection of transplanted kidneys and hearts in combination with steroids and cyclosporine A (2,33,66).…”
mentioning
confidence: 99%
“…IMPDH inhibitors are expected to mainly affect viral RNA and/or DNA synthesis when there is an increased need for synthesis, as in the case of virus-infected cells. IMPDH inhibition decreases levels of intracellular guanine nucleotide pools required for adequate RNA and DNA synthesis; therefore, inhibition of IMPDH with MPA has been shown to have antiproliferative (7), immunosuppressive (42), antimicrobial (43), antiviral (63,70), and antiparasitic (3,29) effects. Currently, MPA is used clinically to prevent rejection of transplanted kidneys and hearts in combination with steroids and cyclosporine A (2,33,66).…”
mentioning
confidence: 99%
“…In vitro biochemical studies have shown that the antileishmanial activity of these agents is due to metabolism of the drugs into analogs of inosine and adenosine nucleotides by the organisms (2,6,(12)(13)(14). Inhibition of guanosine nucleotide utilization may also be important for antileishmanial activity since mycophenolic acid, an inhibitor of guanosine monophosphate synthesis from inosine monophosphate, inhibits amastigote multiplication in vitro (4).…”
mentioning
confidence: 99%
“…They could be metabolized as other allopurinol derivatives or as guanine analogs. In the latter case it is noteworthy that inhibition of guanosine nucleotide utilization may be important for antileishmanial activity (13).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of guanosine nucleotide utilization may be important for antileishmanial activity because mycophenolic acid, an inhibitor of GMP synthesis from IMP, inhibits amastigote multiplication in vitro (13).…”
Section: * Corresponding Authormentioning
confidence: 99%